Impact of Large-Scale Energy Storage on the Least-Cost State of Power Systems - Case Study California - Soini, Martin (My University, 2015)
Energy storage is expected soon to become an increasingly important part of electricity systems around the world. This is driven by direct technology-specific policies, the expansion of variable electricity sources based on solar and wind power, and the decreasing capital cost of storage solutions. This report addresses the impact of a large-scale employment of this technology class on the composition and operation of a power system. It thus explores the shifts in value of the generators and their output once the possibility of transferring significant amounts of electric energy between different hours is provided. For this purpose, a stylized version of the power system in California is analyzed and described by a deterministic linear model. The investment in the system is optimized together with the dispatch over one year. To assess the impact of increasing levels of storage power capacity under different carbon cost scenarios, these parameters are varied exogenously. This approach is complemented by two simpler models, which serve to illustrate some more intricate aspects of the system’s behavior. The direct arbitrage mechanism introduced by the operation of the storage causes the value of the generators with the cheapest cost to be higher and consistently leads to the expansion of wind power as well as the increase of electricity production from base load (biomass) power plants. Under some emission cost scenarios the storage-induced rise of wind power capacity results in the reduction of the economic value of base-load power plants and the net increase of the output of gas-fueled peaker plants. The relative competitiveness of wind and solar power is equally affected by an increase of the storage power capacity, which causes the expansion of one of them at the expense of the other in scenarios with high storage capacities. Both the levelized cost and the demand-correlation of the electricity from these variable sources have been found to play a pivotal role in the final outcome.
Keywords: Energi; Hållbar utveckling; Annan teknik; Energy; Sustainable Development; Other Engineering and Technologies